Racial/Ethnic Disparities in Cervical Cancer Screening Services Among Contractors of the Connecticut Breast and Cervical Cancer Early Detection Program - Morgan A. Pratte; Amy Griffin; Amy Griffin; Chioma Ogazi; Susan Yurasevecz; Carol A. Blanks; Lisa McCooey; Joy S. Kaufman; Joy S. Kaufman (Mary Ann Liebert, 2018)
Purpose: Racial/ethnic minority women are at increased risk for cervical cancer. The objective of this study is to use performance management data from the Connecticut Breast and Cervical Cancer Early Detection Program (CBCCEDP) to determine whether race/ethnicity disparities exist in human papillomavirus (HPV) co-testing uptake across CBCCEDP contractors. Methods: Secondary analysis of Connecticut's Minimum Data Elements data for 2013?2015 among 10 contractors participating in the CBCCEDP. Participants included women aged 30?64 years and eligible to receive routine cervical cancer screening services through the CBCCEDP (n=5,262). HPV co-testing uptake was compared across contractors and race/ethnicity groups within each contractor using chi-square and Fisher's exact tests as appropriate. Results: Overall, 62.9% of women received HPV co-testing services. Significant differences in co-testing rates were detected between racial/ethnic groups when data were examined across all contractors (p<0.001). Black women were least likely to receive co-testing (49.1%), while Hispanic women were most likely to receive co-testing (68.2%). When data were examined at the individual contractor level, significant differences between racial/ethnic groups were observed in 50% of the contractors. Conclusions: This study identified racial/ethnic disparities in uptake of HPV co-testing both overall and within individual contractors involved in the CBCCEDP. These findings will be used to guide program improvement with the goal of increasing quality and consistency of care for all women seeking screening services.